(untitled) - Denniston , Katherine J (New York, 2007)
The fifth edition of General, Organic, and Biochemistry is designed to help undergraduate health-related majors, and students of all other majors, understand key concepts and appreciate the significant connections between chemistry, health, disease, and the treatment of disease. This text continues to strike a balance between theoretical and practical chemistry, while emphasizing material that is unique to health-related studies.
Keywords: Chemistry, Organic,Biochemistry,Hoá học, hữu cơ, sách giáo khoa